Oil palm empty fruit bunch biochar and compost as amendment for improvement of polybag-growing media and oil palm seedlings - Radin, Rovica (2017)
The common practice of growing oil palm seedlings in the main nursery is using top soils as growing medium. These soils especially in tropical region are highly-weathered acidic soils, and low in soil organic matter content. Soil amendment using organic materials such as biochar or/and compost may potentially improve the soil physicochemical properties, promote plant growth and enhance rooting process. Both compost and biochar production are methods to recycle organic wastes and add carbon for sustainability of oil palm industry. Thus, the general aim of this study was to investigate the effects of oil palm empty fruit bunch (EFB) biochar and compost as amendment of polybag growing medium on oil palm seedlings in the main nursery stage. A field study was conducted with treatments of four rates of biochar (biochar was applied according to weight percentage of C added to polybag mixture; 0, 0.5, 1.0 and 1.5% w/w C (biochar C: soil mixture)), two compost rates (0 and 30% v/v) and three rates of fertilizer application (50, 75 and 100% of fertilizer recommended rate) laid out in randomized complete block design (RCBD) design with four replications. The effects of biochar, compost, and biochar-compost on oil palm seedling growth was evaluated and the effectiveness of EFB biochar in retaining soil nutrients to reduce nutrients leaching was determined indirectly by measuring nutrients leached. In addition, an incubation study was carried out in laboratory to investigate the effects of EFB biochar on soil carbon and nitrogen mineralisation over a period of 270 days. This laboratory study consisted of same compost and biochar rates as in field study (two compost rates and four biochar rates). Results showed that oil palm shoot dry weight responded to quadratic relationship with increasing biochar rates in media with and without compost amendment, with shoot biomass comparable to the control (media without amendment). However, the higher root dry weight was obtained with 1.5% C addition in growing media with 30% v/v compost and applied with 75% fertilizer rates. Regression analysis showed positive response for height, bole diameter and number of frond production to biochar application rates with or without compost.